An IrIV-containing polyoxometalate. Issue 7 (3rd December 2014) - Adonin, Sergey A.; Izarova, Natalya V.; Besson, Claire; Abramov, Pavel A.; Santiago-Schübel, Beatrix; Kögerler, Paul; Fedin, Vladimir P.; Sokolov, Maxim N.
Abstract : In situ formation of Ir(iv ) oxo-hydroxo complexes, coupled with a gradual release of tungstate ions, results in the redox-active Anderson–Evans-type polyanion [Ir IV W6 O24 ] 8− . Abstract : [HIr IV W6 O24 ] 7−, representing the first Ir-containing Anderson–Evans-type polyanion and the first structurally characterized Ir IV -based polyoxometalate, has been isolated as its hydrated sodium salt and characterized by single-crystal X-ray diffraction, mass spectrometry, and IR, UV-Vis and EPR spectroscopy. Cyclic voltammetry indicates that the Ir IV ions in [HIrW6 O24 ] 7− can undergo reversible one-electron reduction and oxidation, resulting in Ir III and Ir V derivatives.